Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jace.17753
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the fundamentals of rehydroxylation dating of archaeological ceramics via NMR and IR microscopy

Abstract: Chronology assumes a central role in the process of historical and archaeological reconstruction by allowing us to time the change and development of human societies. Dating provides a framework for linking individual events together. It is the backbone for historical narratives, and connections between environmental and archaeological records on a global scale. However, until today, establishing a reliable chronology for ancient human societies and civilizations using pottery has remained one of the most cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(35 citation statements)
references
References 70 publications
(155 reference statements)
2
33
0
Order By: Relevance
“…Beidellite is a swelling material. We determined the exchange time of the beidellite interlayer H 2 O T1-water with additional adsorbed D 2 O T0-water in the previous study 4 as τ = 125 s ± 35 s by means of an equation similar to eq 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Beidellite is a swelling material. We determined the exchange time of the beidellite interlayer H 2 O T1-water with additional adsorbed D 2 O T0-water in the previous study 4 as τ = 125 s ± 35 s by means of an equation similar to eq 1.…”
Section: Resultsmentioning
confidence: 99%
“…We determined a mean exchange time of τ = 64 h at 350 °C for illite, and activation energies of 39 kJ mol −1 for illite and 36 kJ mol −1 for beidellite in the respective temperature interval. 4 Our considerations have been based on the assumption that the structure of the material does not change during the H/D exchange (hydrothermal treatment) at these temperatures. However, new experiments showed that structures of the material decline in dependence on the exchange time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations